A genealogy of lesbian feminisms in New Zealand: Some implications for young lesbian health and wellbeing - Katie Palmer du Preez; Deborah Payne; Lynne Giddings (University of Ottawa, 2020)
In the 1970s, radical lesbian feminists identifi ed heterosexuality as a socially glorifi ed state of being, and organised to resist social pressure to conform to heteronorms. Decentring of radical feminist discourse has been linked to a 'shrinking lesbian world', with implications for the health and wellbeing of young women who identify as lesbian. This article employs a poststructural feminist perspective, and Foucault's notions of discourse and genealogy. Two sets of data were analysed: issues of Aotearoa New Zealand feminist periodical Broadsheet published 1972-1976, and interviews with 15 young lesbian women conducted in 2012. Findings explore how radical lesbian discourse was marginalised, and some of the implications for the health and wellbeing of young lesbian identifi ed women. Compulsory heterosexuality persists as a health and wellbeing issue which produces 'sexual minority stress' and legitimises discrimination, violence and harassment. Marginalisation of radical lesbian discourse via compulsory family status operates to limit opportunities for collective and public lesbian resistance.